1980
DOI: 10.1542/peds.65.4.847
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Instructions for Infants

Abstract: Children less than 3 years old are most vulnerable to drowning, and organized efforts to reduce the toll are indicated. Heretofore, swimming instruction has concentration on school-aged children, but in recent years some emphasis has been placed on teaching younger children to swim, even during the first year of life. Although it may be possible to teach young infants to propel themselves and keep their heads above water, infants cannot be expected to learn the elements of water safety or to rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…As initially proposed by the AAP (Flynn et al, 1980), the current findings suggest that baby swimming programs may increase the risk of drowning among young children, but not in our opinion because they offer caregivers a false sense of security and overconfidence of their babies' swimming skills, an argument later dismissed by Morrongiello and colleagues (2013). Instead, we suggest that experience in baby swimming programs may offer infants a false sense of confidence and security to explore the aquatic environment that leads them to risk going deeper and deeper into the water only when the access is smooth, gradual, and playful.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…As initially proposed by the AAP (Flynn et al, 1980), the current findings suggest that baby swimming programs may increase the risk of drowning among young children, but not in our opinion because they offer caregivers a false sense of security and overconfidence of their babies' swimming skills, an argument later dismissed by Morrongiello and colleagues (2013). Instead, we suggest that experience in baby swimming programs may offer infants a false sense of confidence and security to explore the aquatic environment that leads them to risk going deeper and deeper into the water only when the access is smooth, gradual, and playful.…”
Section: Discussionmentioning
confidence: 53%
“…The AAP initially advised that children should only start swimming programs after the age of 3 years; first because no evidence existed to determine if swimming programs for very young children would increase or decrease the likelihood of drowning and, second, because enrolling babies in swimming programs could develop a false sense of security in caregivers and a consequent reduction of proper supervision (Committee on Sports Medicine & Fitness, 2000; Flynn et al., 1980). They also expressed concern that baby swimming programs could “reduce a child's fear of water and unwittingly encourage the child to enter the water without supervision” (Committee on Injury, Violence, and Poison Prevention, 2010, p. 179).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AAP initially advised that children should only start swimming programs after the age of 3 years; first because no evidence existed to determine if swimming programs for very young children would impact the likelihood of drowning and, second, because enrolling babies in swimming programs could develop a false sense of security in caregivers and a consequent reduction of proper supervision [8,9]. They also expressed concern that baby swimming programs could "reduce a child's fear of water and unwittingly encourage the child to enter the water without supervision" [10] (p179).…”
Section: Introductionmentioning
confidence: 99%
“…A lingering concern is that parents might overestimate their babies' swimming skills and neglect responsibility for close supervision because their children are enrolled in swimming programs [8,9]. Indeed, Morrongiello and colleagues [13] reported that parents' judgment of their young children's swimming skills tends to be poor, even when they are enrolled in swimming programs, and they underestimate their need for supervision.…”
Section: Introductionmentioning
confidence: 99%